Biaryl-functionalization of MXenes toward electrically conductive EMI-shielding polymer composites with low percolation threshold - Ko, Tae Yun; Hong, Junpyo; Lee, Juyun; Oh, Taegon; Lee, Albert S.; Kim, Seon Joon (Elsevier BV, 2025)
The escalating density of electronic devices and wireless technologies has heightened the need for effective electromagnetic interference (EMI) shielding solutions. Conventional polymer-based composites face persistent limitations due to the insulating nature of polymers and poor compatibility between hydrophilic conductive fillers like MXenes and hydrophobic polymer matrices. Here, we report a strategy to overcome this challenge by biaryl-functionalizing Ti3C2Tx MXene with 1,1 '-bi-2-naphthol (BINOL), yielding BINOL-grafted MXene (BIMX) with markedly enhanced dispersibility in a wide range of industrial organic solvents. The resulting BIMX demonstrates excellent compatibility with thermoplastic polyurethane (TPU) and enables the scalable fabrication of nanocomposites through simple solution mixing and blade coating techniques. BIMX/TPU composites exhibit a remarkably low electrical percolation threshold of 0.3 vol% and high electrical conductivity, achieving outstanding EMI shielding effectiveness across X-, Ka-, and W-band frequencies. Structural and spectroscopic analyses confirm the successful grafting and homogeneous dispersion of BIMX within polymer matrices. Furthermore, BIMX is compatible with multiple thermoplastic polymers, enabling versatile form factors for practical applications. This work presents a scalable, solvent-compatible pathway for engineering highperformance, flexible EMI shielding materials, offering a viable solution for next-generation electronics and mobility systems.